Impact of FIFA 11+ and Harmoknee warm-up protocols on coordination and change of direction performance in football athletes - Gao, X.; Li, J.; Cui, X.; Liu, C.; Wang, P. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Objective This study aimed to compare the intervention effects of the FIFA11 + and Harmoknee warm-up programs on the coordination and change-of-direction abilities (COD) of college soccer players.